Enhancing reading achievement through a timed reading approach: A quasi-experimental study in the Saudi EFL context - Abduljalil Hazaea (Australian Journal of Applied Linguistics)
This study implements a timed reading (TR) approach as a scaffolding teaching and learning method to enhance reading achievement and strategies within the Saudi English as a foreign language (EFL) context. The study adopted TR intervention in which processes of EFL reading are scaffolded with those of getting a driving license. The study employs a quasi-experimental design among preparatory year (PY) students at Najran University. The control group consists of 1628 students enrolled in 2023. The quasi-experimental group consists of 1218 students enrolled in 2024. In this intervention, the syllabus breakdown was modified to serve TR. Both language instructors and the students of the experimental group were oriented and trained on the techniques of TR. The data was collected from the course portfolios of 2023 and 2024 for a quantitative report of the results. The results showed that TR has positively enhanced students’ reading achievement. The average achievement level of the course learning outcomes of the experimental group reached 84% compared with 70.49 % in the control group. As for the reading strategies, the experimental group outperformed those of the control group in terms of vocabulary building (+22.05%), inferring meaning between the lines (+23.45%) skimming and scanning (+14.92%). However, the control group outperformed the quasi-experimental group (-1.10 %) in paragraph understanding. This study has insights into the feasibility and benefits of TR in EFL reading instruction, with implications for curriculum development and language learning strategies in Saudi Arabia and beyond.